One class of semilinear Sobolev type equations and phase spaces - Sviridyuk, G.A. (Нелинейные граничные задачи, 2004)
The solvability of the Cauchy problem u(0) = u₀ of an semilinear differential operator equation Lû = Mu + N(u) is under consideration. The abstract results are illustrated by the Cauchy - Dirichlet problem for the Hoff equation and for the Oskolkov equations.